2019
DOI: 10.1177/2374373519851003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices Toward Routine Medical Checkup Among Middle-Aged and Elderly People of Riyadh

Abstract: Introduction: Routine checkup is a form of preventive medicine, it’s a helpful practice to promote health in the community. Studying the prevalence of routine checkup, awareness, influencing, and preventing factors for it in our community will be a helpful tool for the health authorities to promote among individuals. Methodology: This cross-sectional study was conducted in different locations of Riyadh using a convenience sampling technique, with sample size of 414 Saudi participants of both genders aged 36 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 10 publications
5
41
4
1
Order By: Relevance
“…Routine medical check-up plays an essential role in health care. A routine medical check-up can be defined as “a routine health-care process usually done by health-care facilities for both genders and for all age groups at different periods according to the patient risk factors” [ 16 ]. Globally, the frequency of routine medical check-ups varies from country to country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine medical check-up plays an essential role in health care. A routine medical check-up can be defined as “a routine health-care process usually done by health-care facilities for both genders and for all age groups at different periods according to the patient risk factors” [ 16 ]. Globally, the frequency of routine medical check-ups varies from country to country.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the percentage of periodic health examinations is 50.8% for men and 49.8% for women [ 17 ]. Meanwhile, in Saudi Arabia, only 34.3% of middle-aged and older adults have routine medical check-ups [ 16 ]. In Japan, the proportion of people aged 48 and over with routine medical check-ups is 38.4% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed the positive association between education and routine medical check-up among older adults [36], [37]. Education enhances knowledge about the importance of routine health check-ups, which further brings a positive change in attitude and practice of routine medical check-ups among older adults [28]. Results profoundly concluded that older adults with chronic diseases were around 7.7 times more likely to opt for a routine medical check-up than their counterparts.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, studies have examined health-seeking behavior among older adults in combination with various ageingrelated diseases [23]- [25]. We were able to find a few studies examining medical check-ups among people in other countries, not specifically older adults and routine medical check-ups [22], [26]- [28]; however, we were unable to find any study in Indian context examining the prevalence and factors associated with routine medical check-up among older adults in India.…”
Section: Discussionmentioning
confidence: 77%
“…Our study also found that people who underwent health check-ups annually were less likely to start using injection drugs. This nding may not necessarily demonstrate a causal relationship between health screening speci cally and diabetes incidence; it may be attributed to the fact that people who are more concerned about their health are more likely to undergo health check-ups more frequently [19]. However, previous studies have suggested that health check-ups might be useful in screening for lifestyle-related diseases to a certain extent [20][21][22], and it will continue to play a role in preventing the onset and worsening of diabetes if appropriate interventions are implemented.…”
Section: Discussionmentioning
confidence: 92%